The Myths of the Popol Vuh in Cosmology, Art, and Ritual - Sachse, Frauke; Christenson, Allen J., 1957-; Moyes, Holley (Book collections on Project MUSE., 2021)
"Integrated and comparative approach to the Popol vuh, analyzing myths to elucidate ancient Maya past using archaeological and ethnographic information to shed light on the text. Combining interpretations of myths with analyses of archaeological, iconographic, epigraphic, and ethnographic resources, demonstrates how mythologies contribute to the analysis and interpretation"--